Human genome epidemiology : a scientific foundation for using genetic information to improve health and prevent disease - Khoury, Muin J.; Little, Julian; Burke, Wylie (Oxford University Press, 2004)
Describes the important role that epidemiologic methods play in the continuum from gene discovery to the development and application of genetic tests. It proceeds systematically from the fundamentals of genome technology and gene discovery, to epidemiologic approaches to gene characterization in the population, to the evaluation of genetic tests and their use in health services. These methodologic approaches are then illustrated with several disease-specific case studies.